Analisis Jiwa Kewarganegaraan Generasi Muda Indonesia di Era Digital Serta Dampaknya Bagi Bangsa dan Negara - Yitzhak Edmund Tio Manalu; Fatma Ulfatun Najicha (Journal Pendidikan Ilmu Pengetahuan Sosial, 2022)
Citizenship is one of the Behaviour of oneself that collectively commune to shape a community of citizens of a nation which is solid and relying onto each other. Citizenship gives a base fondation for a nation to stand still with the full support of groups of citizens living in a nation itself. Every country will always face the revolutionary changes made by the new generations, regardless Indonesia. Especially, due to the massive improvements on digital technologies that help youth to grow faster into a better being. The implementation of citizenship of Indonesian youths requires a lot of attention in order to increase the certainty of their quality to prepare the youths to fortify the pillars of nationality. To keep the youths’ consistency to hold tight their mindset of citizenship is the responsibility of every layer of a nation, starting from government, society, and the youths themselves.